Semiotic analysis to the cultural content in the EFL textbook - Nuriah Fadliah Husain; Muhammad Zuhri Dj.; Musfirah Musfirah (International Journal of Research on English Teaching and Applied Linguistics, 2021)
This research studied an EFL textbook entitled “Be smart in English for grade X of Senior High School Linguistics and Cultural Studies” to find out two things within it. Those are the types of culture and cultural meaning represented through its texts and images within the EFL textbook. To determine the types of culture, the researcher uses categorization proposed by Cortazzi and Jin while to reveal the cultural meaning, the researcher uses Pierce’s semiotic principal. The researcher conducts a descriptive qualitative research specifically library research because the researcher got the main data from the document review. In addition, semiotic analysis is used in this research to have a complexity analyzing of the cultural sign. The result of this study shows an imbalance portion of cultural content appearance. The percentage shows in four types of cultures that there are 25 of source culture  appearance (21%), 15 times of target culture appearance (13%), 10 times of International culture appearance (8%), and neutral culture appeared as much 69 times (58%). Then, cultural content that has been analyzed using semiotic analysis presented the cultural content appeared majority from image as much 73 times (61%) and texts as much 46 times (39%).